Damage by Tibraca limbativentris (Hemiptera: Pentatomidae) to rice in Southwestern Colombia - Pantoja Lopez, A; Triana Espinel, Mónica; Bastidas López, Harold; García Ardila, C.; Duque E., Myriam Cristina (2007)
Action thresholds for Tibraca limbativentris Stall (TL) on rice were calculated to be 8.8 and 25.8 TL per 10 sweep nets for 30- and 40-day old plants, respectively. Population dynamics of TL at two localities in Valle del Cauca, Colombia, indicated a density of 1.2 TL per sweep (12 TL per 10 sweeps). Densities equal to the calculated action thresholds were not observed in rice fields in Valle del Cauca, Colombia, during the study period. Infestation to 15- or 20-day-old plants did not cause yield reductions, thus suggesting that scouting for this pest should be concentrated on 25- to 40-day-old plants.